New Algorithm of Stress Echocardiography with Adenosine Triphosphate - N. Yu. Nelassov; M. N. Morgunov; R. V. Sidorov; N. S. Doltmurzieva; O. L. Eroshenko; E. A. Arzumanjan; E. L. Kreneva; S. V. Shlyk (Вестник рентгенологии и радиологии)
Objective. Submaximal myocardial hyperemia is known not to be achieved in 16-18% of cases during cardiac stress tests and monotonic intracubital administration of adenosine triphosphate (ATP) at a dose of 140-160 pg/kg/min. The authors set a task to elaborate a new algorithm for stress echocardiography (SEchoCG) with ATP, providing for the possibility of a stepwise increase in the dosage of the drug, as well as to test it in healthy individuals and patients with coronary heart disease (CHD).Material and methods. The authors elaborated a new algorithm for SEchoCG on the basis of an analysis of the main science databases and their first own experience in using ATP during SEchoCG. The key provisions of the new algorithm were: (a) the exercise test consisted of 3 stages (EchoCG data should be recorded before, during, and 5 minutes after ATP infusion); (b) the criterion for achieving submaximal myocardial hyperemia during ATP administration is a systolic blood pressure (SBP) reduction of 5 and more mm Hg; (c) EchoCG was usually recorded at Stage 2 of the test 3 minutes after the start of ATP administration and with a decline in SBP; (d) the initial dose of ATP administration was 140 pg/kg/min; if SBP did not decrease at 3 minutes of the drug administration, the dosage should be first increased up to 175 pg/kg/ min at 1 minute; if there was no effect, the dosage should be increased up to 210 pg/kg/min at another 2-3 minutes. The algorithm was tested in 9 healthy volunteers, and in 26 patients with CHD.Results. Testing the new algorithm showed that all cases achieved submaximal myocardial hyperemia. SBP decreased below 90 mm Hg in 2 patients; 1 patient developed second-degree atrioventricular block; however, a simple decrease in the ATP infusion rate within 30 sec leveled this symptomatology. The SEchoCG data acceptable for the subsequent analysis of myocardial contractility and deformation could be recorded in all the examinees.Conclusion. The new algorithm for SEchoCG with ATP is effective in recording EchoCG findings. To have a final decision on the safety and information value of a new stress test protocol, it may be recommended to further test those in larger groups of patients during SEchoCG and in the use of other imaging procedures to assess myocardial contractility and perfusion.